Validation of road transport statistics through energy effiency calculations - Zachariadis, Theodoros; Samaras, Zissis (My University, 2001)
The paper presents an approach to validate vehicle-kilometre statistics of motor vehicles by comparing them with official energy consumption data. The comparisons were carried out for the 15 European Union countries by computing the energy efficiency and the fuel economy of individual vehicle categories and comparing them with real-world data and model calculations. The major outcome of the study was that estimates of vehicle-kilometres are often unreliable and yield unrealistic energy efficiency and specific fuel consumption results. Based on these conclusions, some basic guidelines are given for energy and road transport analyses: use fuel economy estimates based on measurements of in-use cars under actual driving conditions, collect as many travel data as possible and check their consistency with the aid of energy balances.
Keywords: Industrial economics; Statistical methods; Automobiles